Relationship between Risk Assessment and Compliance to Health and Safety in Ugandan Secondary Schools - Sekiwu, Denis; Kabanda, Milly; Naluwemba, Esther Frances; Tamale Kagwa, Victoria (Donnish Journal of Educational Research and Reviews, 2015)
Health hazards are part and parcel of human life necessitating the provision of safety in every organizational environment (WHO regional Office for Africa, 2004). Likewise, the area of safety and accident prevention is of great concern to school improvement. The study sought to investigate the relationship between Risk Assessment and Compliancy to Health and Safety in Secondary schools in Wakiso District. The study employed a cross sectional survey design on 31 secondary schools. The results established that there is a significant and a positive relationship between risk assessment and compliance to health and safety (r=.56, p≤ 0.05). The study concluded and recommended that, ensuring health and safety requires repetitive assessment of risks so as to minimize hazardous situations. It also demands the collective involvement of educational stakeholders in the task of risk assessment and implementation of health and safety laws and regulations in Ugandan and African Schools.
Keywords: Health and Safety; Occupational hazards; School health and safety